2018
DOI: 10.1007/s10620-018-5377-9
|View full text |Cite
|
Sign up to set email alerts
|

Adding Acotiamide to Gastric Acid Inhibitors Is Effective for Treating Refractory Symptoms in Patients with Non-erosive Reflux Disease

Abstract: Background Approximately 30% of patients who are treated with proton pump inhibitors (PPIs) for gastroesophageal reflux disease (GERD) experience persistent symptoms. No prokinetic agent regiments are useful for symptom relief. Aims This study was conducted to examine the effect of adding acotiamide to PPI or vonoprazan refractory GERD. Methods This was a randomized, prospective, double-blind, placebo-controlled trial. Seventy-one patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…It should be noted that in seven placebo-controlled trials of PPI therapy, the therapeutic gain for regurgitation response averaged 17% compared to placebo; this effect was more than 20% lower than that observed for heartburn (48). Yamashita et al (14) reported that adding gastric acid inhibitors to acotiamide could reduce the total reflux, liquid reflux, and proximal reflux episodes. The combination of omeprazole (20 mg/day) and baclofen showed high improvement in burning and reflux (34).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It should be noted that in seven placebo-controlled trials of PPI therapy, the therapeutic gain for regurgitation response averaged 17% compared to placebo; this effect was more than 20% lower than that observed for heartburn (48). Yamashita et al (14) reported that adding gastric acid inhibitors to acotiamide could reduce the total reflux, liquid reflux, and proximal reflux episodes. The combination of omeprazole (20 mg/day) and baclofen showed high improvement in burning and reflux (34).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, many patients should receive these medications for a long time or even lifelong, which causes side effects such as Clostridium difficile infections (10), kidney problems (11), hip fractures (12), and respiratory infections (13). The symptoms easily relapse after stopping PPIs (1,14). Due to the failure of conventional treatments, a growing interest has been developed in herbal medicine.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 On the other hand, it has been reported that acotiamide reduced regurgitation with transient lower esophageal sphincter relaxation (TLESR) and improved esophageal clearance in healthy subjects, 38 and it ameliorated minor esophageal peristaltic abnormalities observed in healthy subjects. 39 In a recent report on acotiamide, Yamashita et al 40 Abbreviations: NS, not significant; SD, standard deviation. a Data on FD symptom scores after treatment were expressed as mean ± SD.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is limited because early studies had poor enrollment and remain incomplete. 193 Newer agents, such as relamorelin and other ghrelin agonists, are currently under development. 194 These compounds have not yet been studied in patients with both gastroparesis and GERD.…”
Section: What Is the Role For Gastrointestinal Prokinetics In Gerd?mentioning
confidence: 99%